1996
DOI: 10.1007/bf00019102
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of chloroplast glyceraldehyde-3-phosphate dehydrogenase subunits A and B expressed in Escherichia coli: formation of highly active A4 and B4 homotetramers and evidence that aggregation of the B4 complex is mediated by the B subunit carboxy terminus

Abstract: Chloroplast glyceraldehyde-3-phosphate dehydrogenase (phosphorylating, E.C. 1.2.1.13) (GAPDH) of higher plants exists as an A2B2 heterotetramer that catalyses the reductive step of the Calvin cycle. In dark chloroplasts the enzyme exhibits a molecular mass of 600 kDa, whereas in illuminated chloroplasts the molecular mass is altered in favor of the more active 150 kDa form. We have expressed in Escherichia coli proteins corresponding to the mature A and B subunits of spinach chloroplast GAPDH (GapA and GapB, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
84
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 32 publications
5
84
1
Order By: Relevance
“…1C). As a result of what is mentioned above and also the high degree of identity of the C-terminal loop of CP12 to the complex formation mediating C-terminal extension of GAPB (13)(14)(15), we propose that interaction between CP12 and GAPDH occurs at the C-terminal peptide loop of CP12. This suggestion is further supported by coimmunoprecipitation of all the three proteins, using a monospecific antiserum against only one (GAPDH) of them, showing that in this complex, each CP12 molecule is assembled with both of the other enzymes, PRK and GAPDH (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1C). As a result of what is mentioned above and also the high degree of identity of the C-terminal loop of CP12 to the complex formation mediating C-terminal extension of GAPB (13)(14)(15), we propose that interaction between CP12 and GAPDH occurs at the C-terminal peptide loop of CP12. This suggestion is further supported by coimmunoprecipitation of all the three proteins, using a monospecific antiserum against only one (GAPDH) of them, showing that in this complex, each CP12 molecule is assembled with both of the other enzymes, PRK and GAPDH (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…1 A). Because the C-terminal peptide loop is almost identical with a short domain of the C-terminal extension of chloroplast GAPDH subunit GAPB, and this extension was shown to be involved in assembly of four A2B2 tetramers to the hexadecameric A8B8 regulatory form (14,15), we proposed that the peptide loops of CP12 play a role in protein complex formation. Affinity chromatography of stromal protein extracts to overexpressed and immobilized mature CP12 has shown that CP12, indeed, specifically interacts with chloroplast GAPDH in vitro (13).…”
mentioning
confidence: 99%
“…The target for Trx f-mediated dissociation of the PRK/GAPDH/CP12 complex is not yet known, but our finding that PRK can be fully reduced and the complex remain intact suggests that it is unlikely that a change in the redox state of PRK alone is responsible for complex dissociation. There are two further targets for Trx f within the complex, the redox sensitive C-terminal extension on GapB or the cysteine pairs on the CP12 protein (15,16,22,28). However, it is not yet clear whether all three components of the complex need to be reduced for complete dissociation or, whether reduction of either GAPDH or CP12 reduction is the essential step in this process.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to algae, in higher plants the most abundant and active form of chloroplastic GAPDH is a heterotetramer, containing two distinct subunits, GapA and GapB. Thioredoxinmediated redox control of this A 2 B 2 form of GAPDH is mediated by the Gap B subunit, which has a C-terminal extension with homology to the CP12 protein (22,23). Analysis of the PRK/ GAPDH/CP12 complex in leaves indicated that both the A and B forms of GAPDH may be present in this complex (16,24).…”
mentioning
confidence: 99%
“…Mixing experiments with recombinant Rca have shown that the properties of a-Rca are conferred to the heterooligomer, providing a mechanism for redox regulating the Rca holoenzyme (Zhang et al, 2001). In this way, Rca is similar to the chloroplastic glyceraldehyde 3-P dehydrogenase (GAPDH), which also has both redox-regulated (GAP-B) and non-redox-regulated (GAP-A) forms that differ by a C-terminal extension (Baalmann et al, 1996). Like Rca (Zhang and Portis, 1999;Zhang et al, 2001), redox regulation of two Cys residues in the extension exerts master control over the mixed GAPDH oligomer.…”
mentioning
confidence: 99%